2014
DOI: 10.1021/bi500122c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sterol Side Chain on Ion Channel Formation by Amphotericin B in Lipid Bilayers

Abstract: Amphotericin B (AmB) is one of the most efficient antimycotic drugs used in clinical practice. AmB interacts with membrane sterols increasing permeability of fungal membranes; however, it is still unclear how AmB selectively recognizes the fungal sterol, ergosterol (Erg), over other sterols in cell membranes. In this study, we investigated the effect of an Erg side chain on AmB activity by testing a series of Erg analogues that shared the same alicyclic structure as Erg but varied in the side chain structure b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Whilst the mechanism of AmB-ergosterol binding is not fully understood, in vitro analysis of the role of specific functional groups in ergosterol on AmB activity has revealed the importance both the C24-methyl group and 5(6)-7(8) double bond conjugation [16,17]. The former was suggested to promote Van der Waals interactions with AmB within the membrane [17], whereas the latter influences the rigidity of the ergosterol ring system, the structure thought to mediate Van der Waals interactions with the AmB heptaene moiety [46]. Therefore, in both cases, sterol changes could directly affect AmB binding, thus reducing its activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the mechanism of AmB-ergosterol binding is not fully understood, in vitro analysis of the role of specific functional groups in ergosterol on AmB activity has revealed the importance both the C24-methyl group and 5(6)-7(8) double bond conjugation [16,17]. The former was suggested to promote Van der Waals interactions with AmB within the membrane [17], whereas the latter influences the rigidity of the ergosterol ring system, the structure thought to mediate Van der Waals interactions with the AmB heptaene moiety [46]. Therefore, in both cases, sterol changes could directly affect AmB binding, thus reducing its activity.…”
Section: Discussionmentioning
confidence: 99%
“…AmB exhibits specific cidal activity against Leishmania , as well as fungi, through interaction with ergosterol and close structural relatives, the major membrane sterol components in these organisms. Binding to cholesterol, the primary mammalian membrane sterol, is less avid due to its lacking conjugated 5(6)-7(8) double bonds in the ring structure (cholesterol has only a 5(6) double bond), and also methylation at the C24 position found in ergosterol [16,17]. Selection for AmB resistance in Leishmania in the cultured promastigote form has revealed loss of ergosterol-like sterols and accumulation of intermediates lacking one or both of these features in resistant lines [1821].…”
Section: Introductionmentioning
confidence: 99%
“…Among clinically approved drugs, azoles inhibit ergosterol biosynthesis and polyene antimycotics, e.g., AmB directly interacts with ergosterol present in the membrane (71,72). We investigated the transcriptional effects of these drugs on osh genes in A. fumigatus.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have reported the SAR results of various sterol analogs, and found that the AmB-ergosterol interaction is probably stabilized by face-face VDW interaction. 7,8 Thus, the gauche-containing conformation induced by 7a-OH-AmB may prevent the VDW contact between the AmB macrolide and sterol, consequently altering the sterol selectivity of 3 ( Fig. 3f/g).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, detailed SAR studies on sterols were conducted to evaluate their hydrophobic interactions. 7,8 For the mycosamine moiety, chemical modification of the C3 0 -amine group revealed that the positive charge of the amine was necessary for its activity. 9 More recent SAR studies disclosed that the C2 0 -OH group affects the sterol selectivity.…”
mentioning
confidence: 99%